CUSTOMER TRUST AND DATA PRIVACY IN DIGITAL BANKING SERVICES - A STUDY IN CONTEXT OF ARTIFICAL INTELLIGENCE - Srivastava, Sunita; Sharma, Shivangi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the relationship between customer trust, data privacy, and artificial intelligence (AI) in digital banking services. As banks increasingly utilize AI for automation, fraud detection, and personalized experiences, concerns over privacy, data security, and ethical usage have grown. This research investigates how perceived security features, customer satisfaction, and AI quality influence customer trust. Using data from 206 respondents, analysed through Spearman’s Rank Correlation, the results show significant positive relationships between security features, AI quality, customer satisfaction, and trust in digital banking. Customers who perceive stronger security measures and higher-quality AI are more likely to trust digital banking platforms. The study highlights the need for transparency in AI processes and robust security measures to strengthen trust. It urges financial institutions and policymakers to balance AI-driven innovations with ethical data handling and privacy protections to sustain and enhance customer confidence in digital banking.